1989
DOI: 10.1177/001872678904200305
|View full text |Cite
|
Sign up to set email alerts
|

Work Values and Organizational Commitment: A Study in the Asian Context

Abstract: This paper seeks to investigate the association between work values and organizational commitment in the Asian context. Two major dimensions of work values, that is, intrinsic and extrinsic, were derived from a factor analysis of Wollack et al.'s scale. Organizational commitment was defined in terms of an individual's degree of identification and involvement in the work organization. This variable was measured using Porter et al.'s scale. The analysis suggested that intrinsic work values relate more closely to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
0
8

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 21 publications
4
48
0
8
Order By: Relevance
“…Elizur and Koslowsky (2001), for example, found that work values, especially cognitive ones, are positively associated with organisational commitment. Similar findings were shown in Asia when Putti et al (1989) …”
Section: Work Valuessupporting
confidence: 87%
See 2 more Smart Citations
“…Elizur and Koslowsky (2001), for example, found that work values, especially cognitive ones, are positively associated with organisational commitment. Similar findings were shown in Asia when Putti et al (1989) …”
Section: Work Valuessupporting
confidence: 87%
“…While general values may refer to any principles, work values specifically focus on principles held in the workplace, for example the importance of money or of working with people. Work values differ enormously among employees and are strong antecedents of organisational commitment (Elizur and Koslowsky, 2001;Putti et al, 1989) and job satisfaction (Cheung and Scherling, 1999;Knoop, 1994).…”
Section: Work Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, work attachment also positively correlated with organizational commitment (Ho, Oldenburg, Day, & Sun, 2012;Dabare & Sajeevanie, 2014;Geldenhuys, Łaba, &Venter, 2014). There are many literatures indicate there was a positive correlation between work value and organizational commitment (Putti, Aryee, & Liang, 2014;Shas, Kaur, & Haque, 1992;Maiyanto & Santhoso, 1999).…”
Section: Introductionmentioning
confidence: 96%
“…These shortcomings make it difficult to evaluate his results. Putti, Aryee and Liang (1989) factor analyzed the OCQ using varimax rotation with Kaiser normalization and found a two factor solution accounting for 46.3% and 9.3% of the variance, respectively. There was no clear pattern to the items loading on the second factor.…”
mentioning
confidence: 99%